A Conceptual Design of Two DoF Crawler Tree Planting Robot with Helical Digging Arm - Tatar, Ahmet Burak; Tanyildizi, Alper K.; Tasar, Beyda (Institute of Electrical and Electronics Engineers Inc., 2023)
In the last decade, technological developments, products, and processes have been used in agricultural activities as well as in all production areas in our world and in our country. Increasing green areas by planting saplings, which is one of the agricultural activities, and preventing climate change by reducing CO2 rates are within the scope of priority areas and green agreements. Planting seedlings quickly and regularly on hundreds of acres of rough land requires high human labor and time and it is costly. It is aimed to carry out this process with a semi-autonomous sapling planting robot due to its advantages such as minimizing manpower activity and cost and providing the opportunity to work 24 hours if necessary. Within the scope of this study, a three-dimensional concept design of a tree planting robot, equipped with a crawler, camera and ultra-dimmer sensor and environmental sensing unit, capable of drilling sequential holes with a spiral soil digging mechanism with a fast and regular lane tracking was made. © 2023 IEEE.
14th International Conference on Mechanical and Intelligent Manufacturing Technologies, ICMIMT 2023 -- 26 May 2023 through 28 May 2023 -- Cape Town -- 191487
Keywords: conceptual design; crawler tree; mechanical model; planting robot